Reflections of Pan-Israelite Identity: A View from the Book of Amos - Krause, Joachim J. (Biblica, 2025)
Pan-Israelite identity, i.e. a shared sense of belonging among Israelites and Judahites, is a time-honored problem on which considerable new light has been shed by recent studies. The present contribution seeks to broaden the biblical evidence. In so doing, it purposefully turns to a literary tradition in which pan-Israelite identity is not quite as readily apparent as it is elsewhere, namely the book of Amos. Exploring two of its most salient features, it is argued that both the Judahite prophet addressing Israel and the Israelite tradition cherished in Judah are manifest reflections of pan-Israelite identity.